Alkaline lignin does not immobilize cadmium in soils but decreases cadmium accumulation in the edible part of lettuce (Lactuca sativa L.). (1st October 2022) - He, Lizhi; Yu, Yijun; Lin, Jiahui; Hong, Zhiqi; Dai, Zhongmin; Liu, Xingmei; Tang, Caixian; Xu, Jianming
Abstract: Heavy metal contamination and low use efficiency of phosphorus (P) fertilizers are worldwide issues. Alkaline lignin is expected to decrease the heavy metal risk and enhance the P availability in heavy-metal-contaminated soils. A 120-day incubation study examined the effects of alkaline lignin on Cd, Pb and P bioavailability and transformation in Cd or Cd/Pb co-contaminated red and cinnamon soils and elucidated the associated mechanisms. A pot experiment further tested Cd accumulation in lettuce ( Lactuca sativa L.) grown in the Cd-contaminated red soil. The amendment of alkaline lignin increased the concentrations of bioavailable Cd by 13–20% in the acid red soil and 97–107% in the alkaline cinnamon soil, respectively, due to the increase of dissolved organic C concentrations. Meanwhile, it also increased the concentrations of available P in both soils, Al–P in the red soil and Ca2 –P in the cinnamon soil. Consequently, alkaline lignin amendment increased lettuce biomass of shoots by 8–23% and of roots by 56–71%, P uptake by 37–50% in shoots and by 28–62% in roots, and limited Cd transport from root to shoot which decreased Cd concentrations by 26% in lettuce shoot (edible part). The results suggest that alkaline lignin increases plant growth and decreases Cd bioaccumulation in the shoot through restricting Cd translocation from the root to shoot and increasing soil P availability but not Cd immobilization, and hence may have potential to reduce vegetable Cd contamination risk. Graphical abstract: Image 1 Highlights: Alkaline lignin increased the Cd mobilization in soils. Inorganic phosphorus bound with Cd or Pb in soils. Alkaline lignin decreased the Cd translocation from lettuce root to shoot. Alkaline lignin increased the lettuce yield through activating soil phosphorus.